[Pt(SCN)4]2–‐Based Coordination Polymers and Supramolecular Squares: Intermolecular Pt···H–C Interactions Probed by Luminescence Spectroscopy at Variable Pressure. Issue 22 (28th March 2017) - Suffren, Yan; Kobayashi, Masayuki; Ovens, Jeffrey S.; Rodrigue‐Witchel, Alexandre; Genre, Caroline; Sakai, Ken; Reber, Christian; Leznoff, Daniel B.
Abstract : The structures of four types of supramolecular systems containing [Pt(SCN)4 ] 2– molecular units have been characterized. [Mn(bipy)2 Pt(SCN)4 ]2 · 2MeOH (1 ) and [Zn(bipy)2 Pt(SCN)4 ]2 · 2MeOH (2 ) show cis ‐thiocyanato ligands bridging the Pt II and Mn II or Zn II ions, leading to a molecular square motif. [Zn(bipy)2 Pt(SCN)4 ]2 (3 ) presents chains where trans ‐thiocyanato ligands bridge the Zn II and Pt II ions. For1 –3, free thiocyanato ligands are coordinated to the Pt II centers to complete the square‐planar coordination. [Pb(bipy)2 Pt(SCN)4 ]2 (4 ) reveals a two‐dimensional sheet structure where all SCN – ligands bridge the Pb II and Pt II ions. [Pb(terpy)Pt(SCN)4 ]2 (5 ) is similar to3, with two bridging trans ‐SCN – ligands and two that are coordinated only to the Pt II centers. For all compounds, d–d luminescence is observed with band maxima at approximately 14600 cm –1 (690 nm). Spectra show characteristic shifts with pressure, indicative of either intramolecular or intermolecular effects, depending on the sign of the shift. The pressure‐dependent shifts for1 –5 show rich variations. A well‐documented shift to higher energy due to metal–ligand bond compression is observed for5 and can be used as a basis for a comparison. Compounds1 –4 show a shift of E max to lower energy with pressures below 10 kbar. A change in sign for the shift of E max occurs at 20, 12, and 10 kbar for1, 2, and3, respectively. For4, only a shift to lower energy is observed. Competing intra‐ and intermolecular effects lead to these variations. Abstract : Coordination polymers based on the Pt(SCN)4 motif show d–d (metal centered) luminescence transitions with a rich variety of variable‐pressure variations.